2009
DOI: 10.1097/ta.0b013e31819d979e
|View full text |Cite
|
Sign up to set email alerts
|

Pro- and Synbiotics to Control Inflammation and Infection in Patients With Multiple Injuries

Abstract: Synbiotics contained in the studied formula decrease significantly the risk for sepsis by bloodstream infections and the occurrence of VAP by A. baumannii. The mechanisms of action might involve direct immunomodulatory effect, prevention of bacterial translocation, or most likely a combination of both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 31 publications
8
79
0
6
Order By: Relevance
“…In line with our study, taking antioxidant supplements containing 10,000 IU beta-carotene, 200 IU alpha-tocopherol, 250 mg vitamin C, 50 mg selenium and 15 mg zinc did not affect plasma CRP concentration in trained men [24]. However, in a study by GiamarellosBourboulis et al [25], synbiotics supplementation for 15 days was accompanied by a reduction of CRP concentrations among subjects who did or did not develop sepsis. Serum beta-carotene…”
Section: Discussionsupporting
confidence: 89%
“…In line with our study, taking antioxidant supplements containing 10,000 IU beta-carotene, 200 IU alpha-tocopherol, 250 mg vitamin C, 50 mg selenium and 15 mg zinc did not affect plasma CRP concentration in trained men [24]. However, in a study by GiamarellosBourboulis et al [25], synbiotics supplementation for 15 days was accompanied by a reduction of CRP concentrations among subjects who did or did not develop sepsis. Serum beta-carotene…”
Section: Discussionsupporting
confidence: 89%
“…However, our previous study showed that multispecies probiotic supplementation resulted in decreased serum hs-CRP levels among diabetic patients for 8 weeks [20]. In addition, the same findings were reported with consumption of a synbiotic food containing L. casei, B. breve, and galacto-oligosaccharides among patients undergoing hepatobiliary resection [38] and with the use of a synbiotic food in patients with severe multiple injuries [39]. The absent effect of synbiotic bread consumption on serum hs-CRP levels in the current study may be the result of different study designs, the dosages of probiotic and inulin used, the patients studied, and the duration of supplementation.…”
Section: Discussionmentioning
confidence: 50%
“…Whilst not reaching statistical significance, patient mortality was also lower in the symbiotic group (14.3% compared to 30% in the placebo group, p ¼ 0.12). A further study by the same group showed a significant reduction in bacteraemia and ventilator-associated pneumonia (VAP) rates with synbiotic use [48].…”
Section: Traumamentioning
confidence: 98%